Geomorphological alteration in relation to anthropic actions in the Caplina riverbed, Tacna, Peru (Agroindustrial Science, 2022)
Natural phenomena are difficult to control and predict, but risk management can prevent and reduce the risks of flooding due to the overflow of the Caplina River. This work seeks to determine the anthropic alterations and geomorphological characteristics of the Caplina river basin that generate a high risk of flooding in its trajectory. Existing information was used regarding the hydraulics of the Caplina river basin, carried out by the Tacna Special Project (PET), National Water Authority (ANA), Local Water Authority (ALA), National Meteorology and Hydrology Service (SENAMHI) and the Geological Mining Metallurgical Institute (INGEMMET). With field work, it was possible to establish thematic maps referring to areas of geomorphological alteration due to anthropic action and crops, which made it possible to determine areas prone to overflow and flooding at critical points. After the evaluation carried out in the study area, it was determined that the study area has a very high level of risk and vulnerability.
Keywords: geomorphological alteration; Caplina basin; geomorphology; hydrology